Arte y Cultura en la transformación de barrios populares en América Latina - Luis Campos; Catherine Paquette (IdeAs)
Latin America has an important tradition of marginalized neighborhood improvement programs. These have undergone a significant evolution over time, shifting from initiatives focusing mainly on the provision of basic services and housing improvement to multisectoral projects giving high priority to citizen participation and to the co-production of urban actions with the resident population. In this context, the use of art and culture as a lever for urban transformation has become increasingly important. But when large urban regeneration projects implemented in city cores or wasteland areas in progress of recovery tend to use art and culture as a way to achieve greater urban competitiveness and to attract new residents and investors, poor neighborhood upgrading programs use this resource in a very different way, as a triggering agent for the social integration of the inhabitants, through project initiatives that seek to activate and maintain their permanent participation and thus, indirectly, generate an urban transformation of the site.The article aims to initiate reflection on the use of art and culture in marginalized neighborhood improvement programs in Latin America, trying to understand the specific nature of their approach to urban issues and thus, contribute to the discussion on a topic that is still little explored.